2022
DOI: 10.4103/aja2021119
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the aging corpus cavernosum by shear wave elastography

Abstract: We wanted to determine whether shear wave elastography (SWE) could be used to evaluate the aging degree of the corpus cavernosum (CC) and to identify the histological basis of changes in SWE measurements during the aging process. We performed a cross-sectional study enrolling healthy participants of different ages. We measured the Young’s modulus (YM) of the penile CCs by SWE and assessed erectile function using the International Index of Erectile Function-5 (IIEF-5). Histological investigation was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We clearly showed that ΔEHS and the efficacy rate based on the judgement by patient satisfaction decreased with aging. Recently, it was reported that Young's modulus of the corpus cavernosum by shear wave elastography correlated positively with age and negatively with EF 24 . That study also showed by histological examination that the corpus cavernosum had increased collagen content but decreased smooth muscle content with increased age 24 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We clearly showed that ΔEHS and the efficacy rate based on the judgement by patient satisfaction decreased with aging. Recently, it was reported that Young's modulus of the corpus cavernosum by shear wave elastography correlated positively with age and negatively with EF 24 . That study also showed by histological examination that the corpus cavernosum had increased collagen content but decreased smooth muscle content with increased age 24 .…”
Section: Discussionmentioning
confidence: 72%
“…Recently, it was reported that Young's modulus of the corpus cavernosum by shear wave elastography correlated positively with age and negatively with EF 24 . That study also showed by histological examination that the corpus cavernosum had increased collagen content but decreased smooth muscle content with increased age 24 . However, we must emphasize that LiESWT was relatively effective even for patients aged 50–60 years (68.6%) and 60–70 years (71.3%) and do not think that an efficacy rate of 44.8% for patients aged over 70 years (73.6 ± 3.1 years) was clinically low.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that pathological changes in the component and content of penile tissue would affect the SWQ value measured by 2D-SWE [ 16 ]. Identifying the main factors affecting the penile SWQ value is the prerequisite for accurate diagnosis of the penile disease using 2D-SWE.…”
Section: Discussionmentioning
confidence: 99%